Nonea dumanii sp. nov. (Boraginaceae) from the Taurus mountains (south Turkey) - Bilgili, Bilgehan; Coppi, Andrea; Selvi, Federico (Wiley, 2012)
The new species Nonea dumanii, endemic to the mountains of the western Taurus in south Turkey (C4 Antalya), is described an illustrated based on original collections by the authors. Karyological observations and analysis of ITS1 DNA sequences showed that the species is probably hexaploid with 2n = 6x = 60 and has phylogenetic affinity to the diploid N. monticola from the Paphlagonian mountains as well as to the tetraploid N. anchusoides from northwest Iran and southeast Turkey. From these allopatric species it is morphologically distinct in characters of the indumentum, flower and fruit. Polyploidy is supported as a major driving force for speciation in Nonea, especially in the group of Anatolian mountain species with primary base number x = 10.
Keywords: 15. Life on land